1977
DOI: 10.1159/000231810
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Antigen-Induced Histamine Release by β-Adrenergic Stimulants <i>in vivo</i>

Abstract: IgE-mediated histamine release was studied using the method of passive peritoneal anaphylaxis (PPA) in the rat. Some β-adrenergic stimulants markedly inhibited this reaction in vivo, the order of potency (ED50μg/kg i. v.) of agents tested being fenoterol (6), salbutamol (40) and isoproterenol (94). Higher activity against the simultaneously measured dye extravasation suggested a dual effect of the drugs on both the cellular (inhibition of histamine release) and the vascular level. The order of poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…As to the mechanism of anti-allergic action of /J-agonists, it is widely accepted that /3-agonists inhibit the release of histamine and other mediators of ana phylaxis from mast cells via elevation of the cellular level of cAMP [2,28], This concept has been sup ported by in vitro [1][2][3][4][5][6][7][8][9] as well as in vivo [29] experi ments. Fiigner [29] demonstrated, using the method of passive peritoneal anaphylaxis in rats, that /3-agonists such as fenoterol, salbutamol and isoproterenol mark edly inhibited IgE-mediated histamine release and dye leakage into the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to the mechanism of anti-allergic action of /J-agonists, it is widely accepted that /3-agonists inhibit the release of histamine and other mediators of ana phylaxis from mast cells via elevation of the cellular level of cAMP [2,28], This concept has been sup ported by in vitro [1][2][3][4][5][6][7][8][9] as well as in vivo [29] experi ments. Fiigner [29] demonstrated, using the method of passive peritoneal anaphylaxis in rats, that /3-agonists such as fenoterol, salbutamol and isoproterenol mark edly inhibited IgE-mediated histamine release and dye leakage into the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Fiigner [29] demonstrated, using the method of passive peritoneal anaphylaxis in rats, that /3-agonists such as fenoterol, salbutamol and isoproterenol mark edly inhibited IgE-mediated histamine release and dye leakage into the peritoneal cavity. In the present work, too, isoproterenol inhibited the release of hista mine, but there was no definite correlation between inhibition of the vascular permeability and inhibition of the histamine release ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to its intraperitoneal injection. DSCG [3] and WY-16.922 which is an orally effective anti allergic agent [13]; they have been demon strated to inhibit histamine release in similar experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of /i-sympathicomimetic drugs in modifying the release of histamine has also been demonstrated in vivo in rats by means of the 'passive peritoneal anaphylax is' (PPA) model [7]. Finally, Lamkin et al [10] and Jorde and Schata [9] have shown that /i-adrenergic drugs inhibit the histamine response in human skin.…”
Section: Discussionmentioning
confidence: 99%